Clinical Application of Mathematical Long Bone Ratios to Calculate Appropriate Donor Limb Lengths in Bilateral Upper Limb Transplantation. (July 2019) - Lutfy, Justyn; Pietak, Alexis; Mendenhall, Shaun D.; Neumeister, Michael W.
Background: Limited methods exist to aid in deciding the appropriate donor limb lengths in bilateral upper limb amputees qualifying for vascularized composite allotransplantation. We hypothesized mathematical equations could be created using long bone length ratios, and applied to radiographs, to approximate the patient's limb length prior to amputation.Methods: A data set of 30 skeletons' unilateral upper limb long bones measured using osteometric board and calipers was used. Anatomic segment ratios were calculated based on humerus length after multivariate linear regression analysis. For clinical application testing, 5 cadavers' upper limbs were radiographed. Radiographic bone lengths were then measured along the long axis of each long bone. These measured radiographic lengths were then compared with the predicted bone lengths, generated from the skeleton data set ratios, for each cadaver.Results: The chi-square goodness-of-fit test showed excellent fit ( P < .01) between the predicted and radiographically measured lengths for the 5 cadavers, and interobserver measurements showed no statistical difference. Depending on the cadaver, percent error in total limb length predicted to measure ranged from 0.9% to 2.7%. The variables to multiply an individual humerus length to calculate a given anatomic segment thus proved to be effective.Conclusions: If a bilateral upper limb amputee has 1 intact humerus, ratios to the humerus length can be reliably applied to calculate the preamputation limb length based on the patient's radiographic humerus length. These formulas are indicated for finding the appropriate limb lengths, and smaller anatomic segments, for donor-recipient matching in upper limb transplantation.